A Study on Amul Doodles before and during the lockdown - Choursia, Mandeep (The journal of contemporary issues in business and government, 2021)
Amul is one of the top leading food brands in India. It is the brand due to which white revolution took place in India. At that time, Amul managed to associate village people to work for the brand and provide milk to their organisation which made Amul the top dairy product brand of the country. The marketing and advertising also helped the company to become the largest milk producer in India. The concept of using mascot Amul girl is one of the innovative ad campaigns. The marketing strategy used by the company is to create doodles on current happening. It helped brand to keep their target audience engaged. Amul creates illustrations on current events/ awareness issues and communicates through newspapers or social platforms to the consumers. Presently when there is a complete lockdown in the world due to COVID-19, the brand is spreading awareness on Coronavirus. It is dedicating its doodles to frontline fighters or people working from home to motivate them for their work. In this case study, the researcher closely observed the Amul campaign before and during the lockdown. The researcher analysed the Amul doodles posted in last 3 months that is February, March and April.